A Comparative Analysis of Profitability of Cotton Production under Contract and Non-Contract Farming (Global Journal of Science Frontier Research, 2012)
It has been widely argued that agriculture is undergoing a process of vertical integration with allied industries to which contract farming is most acceptable. As a continually evolving process, contract farming has taken many dimensions and has become the most popular issue in cotton production. An analysis was done on 50 Zaka district cotton farmers inorder to come up with the real operations on the ground concerning cotton production by the smallholder communal farmers. The rationale was to compare the two farming systems in terms of productivity and viability of cotton production concerning contracted and self funded farmers. Questionnaires and interviews were used in data collection whilst the respondents were the sampled farmers from Zaka district to obtain primary data. Agritex, Cottco and Windmill were the sources of secondary data about production trends and activities in the district. The data was analyzed using the t-test and profitability ratios. The difference in yield of the two groups of farmers was insignificant considering the two seasons.
Keywords: smallholder; communal; production